1982
DOI: 10.1111/j.1467-1770.1982.tb00520.x
|View full text |Cite
|
Sign up to set email alerts
|

MARKEDNESS IN SECOND LANGUAGE ACQUISITION1

Abstract: Second language acquisition research to date has applied markedness concepts largely to L1‐L2 transfer, and this work is briefly summarized. Yet there is a neglected potential for such application to ongoing L2 developmental research as well. As an illustration of this, the data from three different studies are reanalyzed in order to show that an otherwise unexplained order of acquisition can be accounted for from a markedness perspective. There is still a need, however, for looking beyond the distributional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…Eckman (1981) showed that marked items in a language will be more difficult to acquire than unmarked ones, and that degrees of markedness will correspond to degrees of difficulty. Rutherford (1982) used markedness theory to explain why there seems to be a certain order of acquisition of morphemes in English: marked structures are acquired later than unmarked structures. In this study, the (es) morpheme is the marked, more complex member with one more feature (e) and less distribution that is more difficult to acquire in comparison with the unmarked member (s) that has wider range of distribution and is less complex to acquire.…”
Section: Morphological Awarenessmentioning
confidence: 99%
“…Eckman (1981) showed that marked items in a language will be more difficult to acquire than unmarked ones, and that degrees of markedness will correspond to degrees of difficulty. Rutherford (1982) used markedness theory to explain why there seems to be a certain order of acquisition of morphemes in English: marked structures are acquired later than unmarked structures. In this study, the (es) morpheme is the marked, more complex member with one more feature (e) and less distribution that is more difficult to acquire in comparison with the unmarked member (s) that has wider range of distribution and is less complex to acquire.…”
Section: Morphological Awarenessmentioning
confidence: 99%
“…O n e area in which more research is needed is in defining markedness relations, both typologically and according to other definitions of markedness (Rutherford, 1982).…”
Section: Problemsmentioning
confidence: 99%
“…in an environment or position of neutralization. Rutherford (1982) reviews most of the researches to data which have utilized the explanatory power of markedness theory in an attempt to understand second language acquisition, thus sheds light on several other studies whose results have greater meaning when markedness considerations are taken into account. A few examples would illustrate the point.…”
Section: Contextual Neutralizationmentioning
confidence: 99%
“…Markedness for Kellerman has psychological meaning, in that "a structure or meaning will be marked in the NL if there are related syntactic structures which express the same message in psychologically simpler ways, or meanings of the same word or lexical unit which the native speaker considers more central" (Kellerman 1979: 38, cited in White 1987). Unfortunately, psychological markedness is hard to define independently and, as pointed out by Rutherford (1982), it tends to be circular (something is difficult, therefore marked; something is marked, therefore difficult). The formal learnability and implicational views of markedness, on the other hand, have the advantage of providing definitions that make use of independent criteria.…”
Section: Psychological Markednessmentioning
confidence: 99%